The Use of Amicable Settlement for Resolving Medical Malparctice in Indonesia - Susila, Muh Endriyo (Medicine, Law & Society, 2021)
Massive publicity on alleged medical malpractice cases has created hostile environment within the health care setting in Indonesia. The unexpected practice of defensive medicine would be possible in response to the rise of medical malpractice litigation. Although it has many negative implications, litigating medical malpractice dispute is preferable for many injured patients. Dispute resolution mechanisms should be introduced and promoted in Indonesia as an alternative to the litigation process with hope of providing redress to victims of medical malpractice in a more amicable manner. This paper aims at exploring the use of amicable settlement method for resolving medical malpractice disputes in Indonesia.